H2O2-Sensitive Isoforms of Drosophila melanogaster TRPA1 Act in Bitter-Sensing Gustatory Neurons to Promote Avoidance of UV During Egg-Laying. Issue 2 (1st February 2017) - Guntur, Ananya R; Gou, Bin; Gu, Pengyu; He, Ruo; Stern, Ulrich; Xiang, Yang; Yang, Chung-Hui
Abstract: The evolutionarily conserved TRPA1 channel can sense various stimuli including temperatures and chemical irritants. Recent results have suggested that specific isoforms of Drosophila TRPA1 (dTRPA1) are UV-sensitive and that their UV sensitivity is due to H2 O2 sensitivity. However, whether such UV sensitivity served any physiological purposes in animal behavior was unclear. Here, we demonstrate that H2 O2 -sensitive dTRPA1 isoforms promote avoidance of UV when adult Drosophila females are selecting sites for egg-laying. First, we show that blind/visionless females are still capable of sensing and avoiding UV during egg-laying when intensity of UV is high yet within the range of natural sunlight. Second, we show that such vision-independent UV avoidance is mediated by a group of bitter-sensing neurons on the proboscis that express H2 O2 -sensitive dTRPA1 isoforms. We show that these bitter-sensing neurons exhibit dTRPA1-dependent UV sensitivity. Importantly, inhibiting activities of these bitter-sensing neurons, reducing their dTRPA1 expression, or reducing their H2 O2 -sensitivity all significantly reduced blind females' UV avoidance, whereas selectively restoring a H2 O2 -sensitive isoform of dTRPA1 in these neurons restored UV avoidance. Lastly, we show that specifically expressing the red-shifted channelrhodopsin CsChrimson in these bitter-sensing neurons promotes egg-laying avoidance of red light, an otherwise neutral cue for egg-laying females. Together, these results demonstrate a physiological role of the UV-sensitive dTRPA1 isoforms, reveal that adult Drosophila possess at least two sensory systems for detecting UV, and uncover an unexpected role of bitter-sensing taste neurons in UV sensing.